Analysis of the Impact of Inclusive Education on the Social Development of Students with Special Needs in Primary Schools - Kirana, Enjel; Zam, Febridho; Raffly Henjilito, Raffly Henjilito (Journal of Foundational Learning and Child Development, 2025)
Purpose of the study: This study aimed to investigate the impact of inclusive education on the social development of students with special needs in primary schools, specifically examining peer interactions, social skills development, and overall social integration. Materials and methods: A quantitative design with a non-experimental approach was employed at Sekolah Luar Biasa Negeri Bangkinang Kota, Riau, Indonesia. Data collection involved Likert-scale questionnaires measuring social development indicators, structured observations of classroom interactions, and interviews with teachers and parents. Statistical analysis was conducted using SPSS. Results: Findings revealed that inclusive education significantly enhanced social development among students with special needs, particularly in areas of peer acceptance, cooperation skills, and self-confidence. Students in inclusive settings demonstrated improved ability to follow social cues, cooperate with peers, and engage in group activities compared to those in segregated learning environments. Conclusions: Inclusive education provides substantial benefits for the social development of students with special needs, creating opportunities for meaningful social interactions and character development. The inclusive approach, when properly implemented with adequate support systems, helps students overcome social and emotional barriers while fostering positive social integration.